2022
DOI: 10.1002/mar.21645
|View full text |Cite
|
Sign up to set email alerts
|

Being there without being there: Gifts compensate for lack of in‐person support

Abstract: Providing social support is a critical part of being in a relationship with someone, but people often struggle to support loved ones in person. In this paper, we show how givers can use gifts to compensate for not providing in‐person social support. Study 1 shows that when it is prohibitively difficult for givers to provide in‐person support, they give more expensive gifts. Study 2 replicates this effect for likelihood to give a gift and shows it is not due to social desirability. Studies 3, 4a, and 4b find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…For example, anthro‐socio‐based research indicates that gift‐giving can serve as a means of “reinforcing relationships that are highly valued but insecure” (Caplow, 1982, p. 383). Psychology‐based research shows that gift‐giving can be motivated by a desire to establish social identities, for instance, a sense of togetherness for a group or family (Klein et al, 2015), and/or by a desire to offer social support (Wiener et al, 2022). Along these same lines, economics‐based work (in particular, game‐theoretic research) indicates that gift‐giving can serve to strengthen the future giver‐recipient relationship (Camerer, 1988; Carmichael & MacLeod, 1997), clarify the current nature of the relationship between the two parties (Camerer, 1988; Prendergast & Stole, 2001), and/or lower overall search costs for a dyad through specialization, that is, allow each member of a dyad to specialize in specific product categories, thereby lowering cumulative search costs (Kaplan & Ruffle, 2009).…”
Section: What Are the Key Motives Of Gift‐givers?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, anthro‐socio‐based research indicates that gift‐giving can serve as a means of “reinforcing relationships that are highly valued but insecure” (Caplow, 1982, p. 383). Psychology‐based research shows that gift‐giving can be motivated by a desire to establish social identities, for instance, a sense of togetherness for a group or family (Klein et al, 2015), and/or by a desire to offer social support (Wiener et al, 2022). Along these same lines, economics‐based work (in particular, game‐theoretic research) indicates that gift‐giving can serve to strengthen the future giver‐recipient relationship (Camerer, 1988; Carmichael & MacLeod, 1997), clarify the current nature of the relationship between the two parties (Camerer, 1988; Prendergast & Stole, 2001), and/or lower overall search costs for a dyad through specialization, that is, allow each member of a dyad to specialize in specific product categories, thereby lowering cumulative search costs (Kaplan & Ruffle, 2009).…”
Section: What Are the Key Motives Of Gift‐givers?mentioning
confidence: 99%
“…Studying gift‐giving with a contemporary focus is important both because doing so makes it most relevant to consumers and marketers in the here and now, and because doing so can produce new understandings about the gift‐giving aspects covered in this review. For example, motivated in part by the fact that the COVID‐19 pandemic made in‐person gatherings quite challenging, Wiener et al (2022) showed how gifts can be used as a substitute for offering in‐person social support; that is, they identified a novel kind of dyadic motive.…”
Section: Key Takeaways and Agendas For Future Researchmentioning
confidence: 99%
“…First, for marketers, ascribing sentimental value to products effectively slows unwanted hedonic adaptation by shifting one's attention from the product attributes to the associations the products possess (Galak & Redden, 2018; Yang & Galak, 2015), which enhances customers' experiences. Second, for consumers, making a sentimentally valuable purchase shows that they consider a significant other important or marks a special event or time (Goodman et al, 2016; Wiener et al, 2022). For instance, consumers buy memorabilia and souvenirs to remember a major occasion (Zauberman et al, 2009), to document an accomplishment (Keinan & Kivetz, 2011), or to signal a close relationship with someone (Liu et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several explanations have been put forth to explain these contradictory findings, such as the suggestion that receiving social support (i.e., enacted support) can cause feelings of dependency, indebtedness, and increased distress (Gleason et al 2003). Another explanation for the ambivalent responses to enacted support is that providing high-quality support during negative life events is challenging and can often backfire (Kaul and Lakey 2003); indeed, recent research shows that people often find it easier to give gifts rather than in-person support during negative life events (Wiener, Howe, and Chartrand 2022). In addition, the literature on social support has highlighted our current lack of understanding about how enacted support contributes to perceptions of social support (Gable et al 2012; Haber et al 2007), meaning that the two are not consistently correlated.…”
Section: Theoretical Backgroundmentioning
confidence: 99%